Analisa Dominasi Konstruksi Epistemologi Pembelajaran Qur’an Hadits, Akidah Akhlak, Fiqih, dan SKI yang diajarkan di Madrasah - Ahmad Mustofa Jalaluddin Al Mahalli (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
Talking about epistemology, can not be separated from the method. The method of Islamic education in this case discusses the nature of the ways of working in compiling the science of Islamic education. Among the methods used in compiling the science of Islamic education, by referring to the main source (al-Qur'an) including the hermeneutic methodology. This study aims to describe the dominance of the epistemological construction of the learning of the Hadith Qur'an, the Akidah of Morals, Fiqh, and the SKI taught in Madrasas. The results of the analysis are concluded: 1.) If Islamic Religious Education is broken down into four subjects, namely the Hadith Qur'an, Akhah Akhlak, Fiqh, and SKI, then it can be determined which epistemology dominates between the sub-subjects. 2.) The Hadith Qur'an emphasizes the bayani epistemology, because the discussion is centered on the interpretation of the Qur'an and Hadith texts. While Akidah Akhlak will be more dominated by Irfani's knowledge, because it focuses on the experience of intuition in the form of psychological beliefs and experiences in the form of attitudes. 3.) The Fiqh will be balanced between the Bayani and Burhani epistemology, because in addition to the study of the text of the postulate which is the subject of the ushul fiqh, it also considers social knowledge concerning correspondence and coherence with the condition of social societies. Likewise, the History of Islamic Culture will be dominated by both epistemologies, because the history of Islam, besides being examined from naqli texts (asbabun nuzul / wurud), also requires conformity between sensory experience and historical texts (both in terms of chronology and periodization)